Intensification of the inverted sugar syrup production using the rotor-pulsation processing - Obodovych, Oleksandr; Shevchenko, Oleksandr; Mironchuk, Valeriy; Lymar, Valerii; Sydorenko, Vitalii; Yakobchuk, Roman (My University, 2021)
The aim of the work is to intensify the process of inverted sugar syrup production using the treatment of water-sugar solution in a rotor-pulsation apparatus. Materials and methods. The aqueous solutions of chemically pure sucrose were used. The studies were conducted using a rotor-pulsation apparatus in the range of flow shear rates from 20×103 s-1 to 50×103 s-1. Determination of carbohydrate content was carried out by high-performance liquid chromatography (HPLC). Results and discussion. The increase in temperature, processing time, and decrease in pH value at a constant flow shear rate led to an increase of the amount of inverted sugar formed. Complete inversion of sucrose occured at a treatment of sugar solution at temperature of 80 °C, pH 3.0, and a flow shear rate of 20×103 s-1 for 30 minutes. At a flow rate of 50×103 s-1 almost all sucrose was hydrolyzed at pH 3.5, and the duration of the process was just 5 minutes under conditions of five-time processing in the rotor-pulsation apparatus in the circulating mode. In the syrup prepared by the proposed technology at a temperature of 70 °C and the duration of treatment 5 minutes, all sucrose in the solution was inverted, and no traces of hydroxymethylfurfural were detected. It is assumed that critical stresses occur at the site of the sucrose chain, and the chemical covalent bonds are broken. The break of these bonds during the process of mechano-chemical destruction occurs on the weakest in terms of energy bonds. As a result of mechano-chemical influence on the section of the sucrose chain (C – O – C), there are critical stresses and the connection is broken. This leads to the formation of free radicals. One radical attaches to the OH- ion and another to the H+ ion forming glucose and fructose. Conclusions. The use of treatment of water-sugar solution in a rotor-pulsation apparatus by the proposed technology allows to intensify process of sugar inversion, namely, reduces the duration of the inversion from 120 to 5 minutes, and ensures almost complete inversion of sucrose excluding the formation of hydroxymethylfurfural.
Keywords: sugar; syrup; inversion; rotor-pulsation; кафедра технологічного обладнання та комп’ютерних технологій проектування